Government and crisis : case study of Indonesia's slow recovery in Asian financial crisis 1997/1998 - Octalira Safitrie (2015)
Asian Financial Crisis 1997/1998 was a red flag in Indonesia's economic development history. The crisis was prominent in becoming a catalyst for Indonesia's future economic development. Not only has the crisis taught the country that the market has its own mechanism to punish poor governance, it also taught the country the importance of good institutions and strong regulatory framework to facilitate resilient economic growth. This literature-based study explores these two lessons by examining the slow recovery process in Indonesia during the Asian Financial Crisis using historical approach. The discussion suggests that Indonesia's domestic politics circumstances were the factor that made the country became the hardest hit crisis country. They were also the factors that hinder the recovery process. Keywords: Asian Financial Crisis, good governance, crisis policy responses